2009
DOI: 10.1029/2009wr008121
|View full text |Cite
|
Sign up to set email alerts
|

Managing population and drought risks using many‐objective water portfolio planning under uncertainty

Abstract: [1] This study contributes a many-objective analysis of the tradeoffs associated with using the portfolio planning approach for managing the urban water supply risks posed by growing population demands and droughts. The analysis focuses on four supply portfolio strategies: (1) portfolios with permanent rights to reservoir inflows, (2) adaptive options contracts added to the permanent rights, (3) rights, options, and leases, and (4) rights, options, and leases subject to a critical reliability constraint used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 66 publications
1
116
0
1
Order By: Relevance
“…In contrast to the objective space, the decision space does not always have a clear topology, as many practical engineering problems contain mixed decision spaces (combinations of real and discrete decision dimensions) and complex decision tree structures (such as those arising from planning applications, e.g. Kasprzyk et al (2009), which require more general approaches to defining topology that are meaningful for behavioural analysis. A second issue concerning the spatial dimension is the characterisation of "spread".…”
Section: Research Challenges and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the objective space, the decision space does not always have a clear topology, as many practical engineering problems contain mixed decision spaces (combinations of real and discrete decision dimensions) and complex decision tree structures (such as those arising from planning applications, e.g. Kasprzyk et al (2009), which require more general approaches to defining topology that are meaningful for behavioural analysis. A second issue concerning the spatial dimension is the characterisation of "spread".…”
Section: Research Challenges and Future Directionsmentioning
confidence: 99%
“…The WRM optimisation approaches where uncertainties are handled in a more explicit way have appeared relatively recently (e.g. Cui and Kuczera, 2005;Deb and Gupta, 2006;Gopalakrishnan et al, 2003;Kasprzyk et al, 2009;Kourakos and Mantoglou, 2008;Labadie, 2004;Mortazavi et al, 2012;Smalley et al, 2000;Tolson et al, 2004;Vasquez et al, 2000).…”
Section: Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the use of many-objective visual analytics in water supply risk management (Kasprzyk et al 2009;Kasprzyk et al 2012) and groundwater monitoring network design (Kollat et al 2011), and have yielded new design insights and demonstrated the potentially highly negative consequences that could result from lower dimensional formulations. The increase in the number of objectives brings new challenges to multiobjective optimization: deterioration of search ability, exponential increase in non-dominated Pareto approximate solutions and difficulty in solution visualization.…”
Section: N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Popular multiobjective genetic algorithms, such as NSGAII (Deb et al 2002), lose their effectiveness as the number of objectives increases, although they have been shown as effective for multi-objective WDS design (Farmani et al 2003). The epsilon Nondominated Sorted Genetic Algorithm II (ε-NSGAII) (Kollat and Reed 2006) has been demonstrated as effective and efficient for solving many objective problems (Kasprzyk et al 2009;Kollat et al 2011, Hadka and Reed in press, Reed et al in press).…”
Section: N O T C O P Y E D I T E Dmentioning
confidence: 99%